Hydrothermal Synthesis and Crystal Structure of A New 3D-Supramolecular Complex: phen2Zn-2N3 - BI, JIAN-HONG; HUANG, ZI-XIAN; KONG, LING-TAO; WANG, HONG-LIANG; HU, NAI-LIANG (Asian Journal of Chemistry, 2010)
The complex phen2Zn-2N3, where phen is 1,10-phenanthroline, has been synthesized and its crystal structure was determined by X-ray diffraction. Crystal data: orthorhombic, space group Fdd2, a = 8.2 05(2) Å, b = 11.052(3) Å, c = 12.508(3) Å, α = 82.852(6) deg, β = 81.899 (6) deg, γ = 73.086(7) deg, V = 1070.2(5) Å3, Mr = 509.84, F(000) = 618, Z = 2, Dc = 1.582Mg/m3, μ = 1.185 mm-1. The final R1 = 0.0406 and wR2 = 0.0828 for 8261 observed reflections (I > 2σ(I)). Zinc(II) ion is coordinated by six atoms in a prolonged octahedron geometry. The compound is in 3-dimensional supramolecular state.